Transcranial magnetic stimulation and transcranial direct current stimulation appear to be safe neuromodulatory techniques useful in the treatment of anxiety disorders and other neuropsychiatric disorders - Aline Iannone; Antonio Pedro de Mello Cruz; Joaquim Pereira Brasil-Neto; Raphael Boechat-Barros (Arquivos de Neuro-Psiquiatria)
ABSTRACT Transcranial magnetic stimulation (TMS) has recently been investigated as a possible adjuvant treatment for many neuropsychiatric disorders, and has already been approved for the treatment of drug-resistant depression in the United States and in Brazil, among other countries. Although its use in other neuropsychiatric disorders is still largely experimental, many physicians have been using it as an off-label add-on therapy for various disorders. More recently, another technique, transcranial direct current stimulation (tDCS), has also become available as a much cheaper and portable alternative to TMS, although its mechanisms of action are different from those of TMS. The use of off-label therapeutic TMS or tDCS tends to occur in the setting of diseases that are notoriously resistant to other treatment modalities. Here we discuss the case of anxiety disorders, namely panic and post-traumatic stress disorders, highlighting the uncertainties and potential problems and benefits of the clinical use of these neuromodulatory techniques at the current stage of knowledge.